THE EXISTENCE OF THE VOLUNTEERS OF THE INDONESIAN HUMANITARIAN COMMITTEE IN DELIVERING INFORMATION ON PREVENTION AND HANDLING COVID-19 - Andre Avila; Rita Herlina (Perkumpulan Dosen Muda (PDM) Bengkulu, 2020)
The existence of volunteers helping the government convey appropriate information to the public either through social media or plunging directly into the field of conducting public communication is the background of this research, with the theme of the Existence of the Volunteers of the Indonesian Humanitarian Committee in Delivering Information on Prevention and Handling Covid-19. This study aims to describe the motivation of volunteers, volunteer activities in the field and forms of volunteer messages on social media. The methodology of this research is descriptive qualitative. Data collection techniques are by interview and document analysis. The results of this study indicate the existence of Indonesian Humanitarian Committee volunteers as the frontline in conveying information on prevention and handling of Covid-19 to the people of South Tangerang, motivated by caring for others as an effort to remind the importance of prevention and handling of Covid 19, in volunteer activities in the field, namely distributing flyers about prevention and handling of Covid-19 through food and food distribution programs, while the form of messages on social media about prevention and handling of Covid-19 is mostly done through Facebook, Instagram, website media, with various messages in the form of articles, photos, status, and messages the other.